STRATEGI DINAS PENDIDIKAN DAN KEBUDAYAAN DALAM MANAJEMEN PEMULIHAN PASCABENCANA BANJIR TERHADAP REHABILITASI INFRASTRUKTUR SEKOLAH TERDAMPAK DI KABUPATEN MANDAILING NATAL - Siti Fatimah Rahmila; Siti Asiyah; Ilham Ramadan Siregar; Muhammad Ali Yusuf; Anisah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Mandailing Natal Regency Education and Culture Office’s strategy for post-flood recovery management focuses on integrating rehabilitation schemes that are both responsive and preventive in nature for affected school infrastructure. This strategy is implemented through cross-sectoral coordination involving the Regional Disaster Management Agency (BPBD) and the Public Works Office to conduct accurate damage assessments as the basis for determining repair priorities. Mandailing Natal Regency is one of the areas in North Sumatra with a high level of vulnerability to flood disasters. These disasters not only impact the economic and social sectors but also damage educational infrastructure, hindering the teaching and learning process. This study aims to analyze the strategies implemented by the Mandailing Natal Regency Education and Culture Office in post-disaster recovery management, particularly regarding the rehabilitation of affected school infrastructure. The research method used is qualitative descriptive. Data collection was conducted through in-depth interviews with the Education Office, principals of affected schools, as well as field observations and documentation related to infrastructure damage reports. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions.